Osmosensation in TRPV2 dominant negative expressing skeletal muscle fibres. (10th August 2015) - Zanou, Nadège; Mondin, Ludivine; Fuster, Clarisse; Seghers, François; Dufour, Inès; de Clippele, Marie; Schakman, Olivier; Tajeddine, Nicolas; Iwata, Yuko; Wakabayashi, Shigeo; Voets, Thomas; Allard, Bruno; et al.
Abstract : Key points: Increased plasma osmolarity induces intracellular water depletion and cell shrinkage (CS) followed by activation of a regulatory volume increase (RVI). In skeletal muscle, the hyperosmotic shock‐induced CS is accompanied by a small membrane depolarization responsible for a release of Ca 2+ from intracellular pools. Hyperosmotic shock also induces phosphorylation of STE20/SPS1‐related proline/alanine‐rich kinase (SPAK). TRPV2 dominant negative expressing fibres challenged with hyperosmotic shock present a slower membrane depolarization, a diminished Ca 2+ response, a smaller RVI response, a decrease in SPAK phosphorylation and defective muscle function. We suggest that hyperosmotic shock induces TRPV2 activation, which accelerates muscle cell depolarization and allows the subsequent Ca 2+ release from the sarcoplasmic reticulum, activation of the Na + –K + –Cl − cotransporter by SPAK, and the RVI response. Abstract: Increased plasma osmolarity induces intracellular water depletion and cell shrinkage followed by activation of a regulatory volume increase (RVI). In skeletal muscle, this is accompanied by transverse tubule (TT) dilatation and by a membrane depolarization responsible for a release of Ca 2+ from intracellular pools. We observed that both hyperosmotic shock‐induced Ca 2+ transients and RVI were inhibited by Gd 3+, ruthenium red and GsMTx4 toxin, three inhibitors of mechanosensitive ion channels. The response was also completely absent in muscle fibres overexpressing a non‐permeant, dominant negative (DN) mutant of the transient receptor potential, V2 isoform (TRPV2) ion channel, suggesting the involvement of TRPV2 or of a TRP isoform susceptible to heterotetramerization with TRPV2. The release of Ca 2+ induced by hyperosmotic shock was increased by cannabidiol, an activator of TRPV2, and decreased by tranilast, an inhibitor of TRPV2, suggesting a role for the TRPV2 channel itself. Hyperosmotic shock‐induced membrane depolarization was impaired in TRPV2‐DN fibres, suggesting that TRPV2 activation triggers the release of Ca 2+ from the sarcoplasmic reticulum by depolarizing TTs. RVI requires the sequential activation of STE20/SPS1‐related proline/alanine‐rich kinase (SPAK) and NKCC1, a Na + –K + –Cl − cotransporter, allowing ion entry and driving osmotic water flow. In fibres overexpressing TRPV2‐DN as well as in fibres in which Ca 2+ transients were abolished by the Ca 2+ chelator BAPTA, the level of P‐SPAK Ser373 in response to hyperosmotic shock was reduced, suggesting a modulation of SPAK phosphorylation by intracellular Ca 2+ . We conclude that TRPV2 is involved in osmosensation in skeletal muscle fibres, acting in concert with P‐SPAK‐activated NKCC1. Abstract :